Predefined clause-based structure to subdue blank node issues - Ting, Mary; Abdul Kadir, Rabiah; Azman, Azreen; Tengku Sembok, Tengku Mohd; Ahmad, Fatimah (IEEE (IEEE Xplore), 2014)
World Wide Web provides vast of resources to the public. Currently, many researches have been done on resources sharing among users through implementation of ontologies. Knowledge in an ontology are represented in the form of triple(s-p-o), where concepts are brought together by a relation. In a situation where there is a need to represent a resource which exist without IRI, blank node can be implemented in placed of the resource. Increase number of blank nodes implemented will increase the complexity of ontology structure. Since it is impossible to avoid blank nodes implementation in the ontology, increase used of it might lead to the intractable of data during the information retrieval. This paper presents a new clause-based structure that able to handle N-ary, container, collection and reified knowledge issues brought by the blank node application. The result shows that the structure able to store complicated knowledge without the need to implement blank node.